Implementasi Nilai-Nilai Adabul 'Alim wal Muta'allim KH. Hasyim Asy'ari dalam Pembentukan Mental Kedisiplinan dan Etika Belajar Siswa (Studi Kasus di SMAN 3 Pulau Rimau) - Amrillah, M. Soinun; Damayanti, Anna; Ariyanto, Muksin; Fauzi, M.; Mansyur, Abu (Riwayat: Educational Journal of History and Humanities, 2025)
This research investigates the implementation of ethical learning values derived from K.H. Hasyim Asy'ari's seminal work, Adabul 'Alim wal Muta'allim (The Etiquette of Teacher and Student), in fostering mental discipline and learning ethics among students at SMAN 3 Pulau Rimau, a public school. The core problem addressed is the erosion of traditional discipline and respect due to digital disruption. Employing a qualitative single case study design, data were collected through in-depth interviews with religious and counseling teachers, classroom observations, and analysis of school disciplinary documents. Data analysis utilized the Miles and Huberman Interactive Model to confirm field findings against the conceptual framework of Adabul 'Alim wal Muta'allim. The results indicate that the school implicitly implements three core adab pillars: adab towards knowledge (seriousness and punctuality), adab towards teachers (respect and obedience), and adab towards peers (cooperation). This implementation successfully contributed to improved student mental discipline, evidenced by a reduction in minor disciplinary cases. In conclusion, while the ethical framework remains relevant for physical discipline, the study finds a significant challenge in translating these values into effective 'digital adab,' particularly concerning respect for teachers in virtual interactions, necessitating explicit policy adaptation in the digital sphere.